2008
DOI: 10.1158/1055-9965.epi-08-0346
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei Related toAnti–B[a]PDE-DNA Adduct in Peripheral Blood Lymphocytes of Heavily Polycyclic Aromatic Hydrocarbon–Exposed Nonsmoking Coke-Oven Workers and Controls

Abstract: Micronuclei (MN) frequency associated to biologically effective dose of polycyclic aromatic hydrocarbons [PAH; anti-benzo[a]pyrene diolepoxide (B[a]PDE)-DNA] within the same subjects' peripheral blood lymphocytes (PBL) was evaluated. Study subjects were nonsmoking male Polish coke-oven workers (n = 49) and matched controls (n = 45) verified for PAH exposure by urinary 1-pyrenol. We found that coke-oven workers, heavily exposed to PAHs (80% workers exceeded the urinary 1-pyrenol biological exposure index value)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 19 publications
(22 reference statements)
4
31
0
Order By: Relevance
“…The PAHs exposure of coke-oven workers in the present study was similar with that in Siwińska et al's and in Zhang's study conducted in coke oven workers and much higher than that reported by Pavanello et al in CMBN assay in coke oven workers (Zhang et al, 2001;Siwińska et al, 2004;Pavanello et al, 2008). Though the length of exposure is not, therefore, the only risk factor (Pavanello et al, 2008). Yang et al reported that the length of time spent outdoors had marginal positive associations with urinary 1-OHP levels in non-occupationally exposed Koreans .…”
Section: Discussionsupporting
confidence: 91%
“…The PAHs exposure of coke-oven workers in the present study was similar with that in Siwińska et al's and in Zhang's study conducted in coke oven workers and much higher than that reported by Pavanello et al in CMBN assay in coke oven workers (Zhang et al, 2001;Siwińska et al, 2004;Pavanello et al, 2008). Though the length of exposure is not, therefore, the only risk factor (Pavanello et al, 2008). Yang et al reported that the length of time spent outdoors had marginal positive associations with urinary 1-OHP levels in non-occupationally exposed Koreans .…”
Section: Discussionsupporting
confidence: 91%
“…The study subjects (n 5 92) included 49 nonsmoking cokeoven workers from 3 Polish cokeries and 43 matched (nationality, gender, smoker status) controls (n 5 43), who had been part of a group of 94 study subjects examined in our previous work 25 for which DNA was still available (enrolment from January through May 2006). Coke-oven workers all had jobs (i.e., charging, coking and pushing operations at the coke-oven battery section) involving exposure to high levels of PAHs.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time as urine was collected, blood samples were taken and placed in EDTAcontaining tubes (20 ml) and evacuated heparin-containing tubes (10 ml) for adduct and MN analysis, as previously described. 25,30 At the Institute of Occupational Medicine and Environmental Health in Sosnowiec: (i) PBL cultures for MN detection were prepared and MN analyses performed; (ii) PBLs for adduct analyses were isolated in Ficoll separating solution (Seromed, Berlin, Germany) within 4 hr after blood collection and kept frozen at 280°C, until they were sent to the Department of Environmental Medicine and Public Health in Padova (Italy), where DNA was extracted. Data on other possible elevated nonoccupational PAH exposure (diet, environment) and consumption of fruit and vegetables were collected by means of a questionnaire, as previously described 23,24 (i.e., high dietary intake of PAHs was the consumption of charcoaled meat (PAH-rich meals) more than once a week; indoor and environmental exposure to PAHs was the use of wood or coal to heat the home, and an index of location of residence that included intense local traffic and presence of industries in the residential area).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included in our analysis indicated that the urinary 1-OHP concentrations in workers with exposure to urban air pollution were all lower than 1 μg/ml, which was different from observed for 1-OHP, the null GSTM1 genotype was associated with a significantly higher micronucleus frequency in both the occupational and non-occupational populations. However, the correlation between internal 1-OHP concentrations and micronucleus frequency was still inconsistent, although occupational PAH exposure was associated with higher micronucleus frequency [64,65]. DNA-adduct levels, but not 1-OHP, concurrently showed dose-response relationship with micronucleus frequency [65].…”
Section: Discussionmentioning
confidence: 98%